Undergraduate Student Perceptions of Faculty Engagement During the Transition to Online Learning - Ty Frederickson; Lori Cooper (Journal of the Scholarship of Teaching and Learning)
Undergraduate students have reported challenges with staying connected to course content, their peers, and to their instructors during the disruption and transition to virtual platforms during the COVID-19 pandemic (Hollister et al., 2022) and there has been a lack of readiness to effectively engage with students and deliver instructional content reported by post-secondary faculty members (Martin et al., 2019) despite a need for relationship-centered teaching.  To investigate these problems, the following study investigated perceptions of faculty engagement practices for undergraduate students who endured this transition in their educational experience.  Using Seif’s learning engagement theory and dimensions of deep learning (2018), seven undergraduate students from one small private institution of higher education in the United States were interviewed to learn more about how faculty engaged them as students during the online transition.  Outcomes included five themes of a) feelings of empathy, b) a perception of, and/or interest in flexibility, c) a recognition that being a part of a learning community was important to their success, d) varying degrees of internal and/or external motivation, and e) real-world applications.  Recommendations for teaching practice as a result of research findings included a focus on relationships, providing rich feedback and clear expectations for students, and making your online teaching memorable for students while adjusting teaching practices to align with the delivery method.  Recommendations for future research included investigating student engagement perspectives in online courses now that the pandemic response has dissipated, how students perceive the shift to online learning has benefitted their learning and engagement, as well as faculty perceptions of how they have engaged learners in online courses.